Keragaan Hasil Produksi Jamur Tiram pada Berbagai Komposisi Substrat - Harnanik, Sri; Sariningtias, Nur Wahyu (Seminar Nasional Lahan Suboptimal, 2022)
Harnanik S, Sariningtias NW.  2022. Yield oyster mushroom with various substrate composition. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 651-659. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).This study aimed to determine effect of log closure techniques on the development of mycelium and effect various subtrate compositions, age of seedlings and cutting log on yield of oyster mushroom. The study was conducted for the 2020-2022 period at KP Kayuagung. The components of the substrate are mixed, put in PP plastic, pasteurized, inoculated, incubated and carried out harvesting two periode. The results showed that technique of closing narrow-mouthed logs causes slow growth of mycelium and even fails to grow. Various additional subtrate components did not significantly affect the yield, but the type of wood affected the timing of the first harvest. The first harvest time in this study ranged from 56 days to 229 days after inoculation. The fresh weight of the first harvest on average ranges from 47.4-138 g . The age of seedlings up to 3 months can still be used.. The log cutting technique can stimulate the formation of mushroom fruits with an average yield range of 32.8 to 46.5 g per log.